Court, credit, and capital : Amsterdam's insolvency legislation in the Dutch golden age / Maurits den Hollander, Tilburg University. - Hollander, Maurits den, 1994- (Studies in legal history ., 2025)
Seventeenth-century Amsterdam was a city of innovations. Explosive economic growth, the expansion of overseas trade, and a high level of religious tolerance sparked great institutional, socioeconomic and legal changes, a period generally known as 'the Dutch Golden Age.' In this book, Maurits den Hollander discusses how insolvency legislation contributed to the rise of a modern commercial order in seventeenth-century Amsterdam. He analyzes the procedure and principles behind Amsterdam's specialized insolvency court (the Desolate Boedelskamer, 1643) from a theoretical perspective as well as through the eyes of citizens whose businesses failed. The Amsterdam authorities created a regulatory environment which solved insolvency more leniently, and thus economically more efficiently, than in previous times or places. Moving beyond the traditional view of insolvency as a moral failure and the debtor as a criminal, the Amsterdam court recognized that business failure was often beyond the insolvent's personal control, and helped restore trust and credit among creditors and debtors.